Open hardware and software robotics competition for additional engagement in ECE students - the Robot@Factory lite case study - Pinto, Vítor H. (2021)
Throughout this paper, a competition created to enable an inter-connection between the academic and industrial paradigms is presented, using Open Hardware and Software. This competition is called Robot at Factory Lite and serves as a case study as an additional enrollment for students to apply knowledge in the fields of programming, perception, motion planning, task planning, autonomous robotic, among others.